2022
DOI: 10.1002/brb3.2826
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the high susceptibility to depression of women during the perimenopause

Abstract: Objective: This study investigated the factors associated with the high susceptibility of perimenopausal women to depression.Methods: A total of 66 perimenopausal women participated in this study. The Zung self-rating depression scale (SDS) was used to evaluate the intensity of depressive symptoms. The modified Kupperman index (KI) was used to assess common perimenopausal symptoms. Psychosocial factors were assessed via the Eysenck Personality Questionnaire, attitudes toward menopause checklist, and metacognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The main lifestyle information was as follows: (1) the intake of a high-salt diet were defined as a diet with high salt intake; (2) the intake of milk/fruit/fish/coffee/eggs was defined as “<3 times/week” or “≥3 times/week”. To evaluate perimenopausal syndrome, we used the modified Kupperman index (mKMI); this index is widely used internationally, including in the People’s Republic of China, and its role in clinical practice is well established [ 11 , 12 ]. The scale comprises 13 items: the weighted score for hot flashes or sweating is 4 points; paraesthesia, insomnia, mood swings, sexual problems, and urinary infection receive 2 points each; and other symptoms receive 1 point each [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main lifestyle information was as follows: (1) the intake of a high-salt diet were defined as a diet with high salt intake; (2) the intake of milk/fruit/fish/coffee/eggs was defined as “<3 times/week” or “≥3 times/week”. To evaluate perimenopausal syndrome, we used the modified Kupperman index (mKMI); this index is widely used internationally, including in the People’s Republic of China, and its role in clinical practice is well established [ 11 , 12 ]. The scale comprises 13 items: the weighted score for hot flashes or sweating is 4 points; paraesthesia, insomnia, mood swings, sexual problems, and urinary infection receive 2 points each; and other symptoms receive 1 point each [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…(10) The results of this test are interpreted as follows: no symptoms from 0 to 16 points, mild symptoms from 17 to 25 points, moderate symptoms from 26 to 30 points and severe symptoms when the score is greater than 30 points. (10,11)…”
Section: Kupperman-blatt Index (Ikb)mentioning
confidence: 99%
“…Studies show that one-third of women with endometriosis suffer from psychological problems and need therapeutic inter-ventions [7]. Depression is more common in women than men, and if women have chronic pain, the risk of depression will be higher [8,9]. A study showed that women with chronic pelvic pain were 1.5 times more depressed than women in the control group [10].…”
Section: Introductionmentioning
confidence: 99%